0200 Trait Mindfulness Moderates the Within-Person Relationship Between Sleep and Pain in Nurses. (27th May 2020) - Mu, C; Lee, S
Abstract: Introduction: Sleep and pain have a bidirectional relationship in clinical populations; however, we know less about the daily association in non-clinical but potentially vulnerable populations. Nurses are prone to poor sleep and pain symptoms due to work schedules and occupational stress. Implications from mindfulness-based interventions suggest that mindfulness may play a role in improving sleep and subsequently, reducing pain. The current study examined the within-person relationship between sleep and pain in nurses, and whether trait mindfulness moderates the relationship. Methods: Participants were 60 nurses employed at a cancer hospital ( M age =35.35±11.83, 32% reported pain). For 14 consecutive days, ecological momentary assessment collected participants' sleep characteristics, pain symptoms (i.e., chest pain, headaches, upset stomach, and other pain), and pain interference with daily activities. Trait mindfulness was measured using the 15-item Mindful Attention Awareness Scale. Multilevel modeling decomposed variances at the between- and within-person levels. Results: At the between-person level, after controlling for sociodemographic covariates, more frequent insomnia symptoms ( β =0.35) or lower sleep sufficiency ( β =-0.19) were associated with more pain symptoms ( p s<.05). Inversely, individuals with more pain symptoms reported lower sleep sufficiency ( β =-0.41, p <.05). At the within-person level, after nights with poorer sleep quality ( β =-0.08, p <.01), lower sleep sufficiency ( β =-0.08, p <.01), or shorter sleep duration ( β =-0.03, p <.05), participants reported more pain symptoms the following day. There were significant interactions of mindfulness with (a) sleep sufficiency predicting pain interference and (b) sleep duration predicting number of pain symptoms, such that the adverse associations of less sufficient and shorter sleep with more pain were more apparent in those with lower mindfulness than those with higher mindfulness. Conclusion: Although there was a bidirectional association between sleep and pain at the between-person level, sleep was more likely to be the predictor of pain at the within-person level in oncology nurses. The significant moderation by mindfulness suggest that promoting mindfulness among nurses, prone to having poor sleep and pain, may reduce the adverse impact of poor sleep on daily pain. Support: This work was supported, in part, by the University of South Florida College of Behavioral & Community Sciences Internal Grant Program (PI: Lee, Grant No. 0134930).